Shades of Green: Environment Activism Around the Globe - Mauch, Christof; Stoltzfus, Nathan; Weiner, Douglas R. (Rowman & Littlefield Publishers, 2006)
Shades of Green examines the impact of political, economic, religious, and scientific institutions on environmental activism around the world. The book highlights the diversity of national, regional and international environmental activism, showing that the term 'environmentalism' covers an entire range of perceptions, values and interests. It demonstrates that each instance of environmental activism is shaped by historically unique circumstances, highlighting within each chapter the ideological, social, and political origins of efforts to protect the environment. Discussing issues unique to different parts of the world, Shades of Green shows that environmentalism around the globe has been strengthened, weakened, or suppressed by a variety of local, national, and international concerns, politics, and social realities.